STUDY OF “RUSUN” TYPOLOGY BASED ON THERMAL COMFORT ANALYSIS USING SOFTWARE SIMULATION METHOD IN RUSUNAWA TYPE-30 - Nurina Vidya Ayuningtyas; Istiani Adianti; Jatmika Adi Suryabrata (Journal of Architecture&ENVIRONMENT, 2019)
Simple rental Flats (Rusunawa) is the government's role in overcoming the need for housing, so that the quality of housing becomes more feasible. The feasibility can be seen from the thermal side of the flat so that the occupants of the flat are more comfortable living in it. This research simulates with software in low-rise apartment buildings so that they get a typology of effective and thermally comfortable flat-panel design. The typology can be a directive for architects in designing a flat which prioritizes thermal comfort for the occupants as well as a flat design that is quite effective and profitable for developers. The software used is Ecotect, Energy Plus, CFD and Dialux. With the simulation software, the double load corridor layout is more effective in terms of development costs and still has a good air exchange. While the orientation of the North-South building is better so that it can reduce the amount of openings from the direction of the coming sunlight.